1973
DOI: 10.1002/aic.690190402
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic specificity

Abstract: SCOPECatalytic specificity refers to the particular ability of a substance or closely related group of substances to catalyze a given type of chemical transformation. Identifying the type of catalyst which is good for a particular reaction is a matter of great practical importance. In the area of heterogeneous catalysis, to which this review is limited, there are few, if any, examples where the factors determining catalytic specificity are understood in detail. However, much progress has been made in establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Experiments carried out with Cu/Ni catalysts of different composition showed that there is a remarkable decrease of (C, C)-bond attack with increasing Cu content, whereas it seems that the (C, H)-bond attack is not strongly influenced by the Cu content. Similar observations have been reported in other reactions [14] [15]. During the reaction of benzyl alcohol considerable catalyst poisoning was observed.…”
Section: Dependence Of Conversion Andselectivity On Reaction Tempersupporting
confidence: 90%
“…Experiments carried out with Cu/Ni catalysts of different composition showed that there is a remarkable decrease of (C, C)-bond attack with increasing Cu content, whereas it seems that the (C, H)-bond attack is not strongly influenced by the Cu content. Similar observations have been reported in other reactions [14] [15]. During the reaction of benzyl alcohol considerable catalyst poisoning was observed.…”
Section: Dependence Of Conversion Andselectivity On Reaction Tempersupporting
confidence: 90%
“…646 and electrical self-stimulation of the brain (13,14). The seemingly ubiquitous nature of catecholamine involvement across a wide spectrum of behaviors and the remarkable adaptive capacity of catecholamines to maintain relatively normal function even in cases of severe damage (1), suggests that catecholamine systems may play a very fundamental role in mediating the interaction between the organism and its environment.…”
Section: Discussionmentioning
confidence: 99%
“…An extremely important feature of heterogeneous catalysis is specificity in relation to the chemical constitution of a surface (14,15). The hydrogenolysis of alkanes provides an excellent example of specificity in catalysis by metals.…”
Section: Catalytic Specificity Of Metalsmentioning
confidence: 99%
“…[2b,10] Thes uccessive demethylation at the terminal CÀC bond is known to occur for cobalt-based catalysts,t hus forming CH 4 and aheavier fragment. [10,11] Thedistributions of the products from n-hexadecane over the catalysts without Brønsted acidity (Table 2a nd Figure S3) suggest ah ydrogenolysis mechanism. Although the addition of Na + onto the Co/SiO 2 decreased its activity for hydrogenolysis (see Table S4), the Co/Na-meso-Y catalyst with Na + in the cation-exchange position showed high hydrogenolysis ability.…”
Section: Methodsmentioning
confidence: 99%
“…Extensive studies have been devoted to developing efficient catalysts for FT synthesis, [1] but the effective control of product selectivity remains one of the grand challenges.T he FT products generally follow the Anderson-Schulz-Flory (ASF) distribution, which is unselective for the middle-distillate products. [1b] Fore xample,t he selectivities of products in gasoline (C [5][6][7][8][9][10][11] and diesel (C 10-20 )f ractions are limited to 45 and 39 %, respectively.Conventionally,the FT products are subjected to further hydrotreatment to increase liquid fuel selectivity. Compared to this two-stage process,the direct production of specific-range liquid fuels would be more energy and cost efficient.…”
Section: Impact Of Hydrogenolysis On the Selectivity Of The Fischer-tmentioning
confidence: 99%